Ultrafiltration-profiled hemodialysis to reduce dialysis-related cardiovascular stress: Study protocol for a randomized controlled trial - Tugman, Matthew J. (Contemp Clin Trials Commun, 2019)
Rapid fluid removal (ultrafiltration, UF) is associated with higher cardiovascular morbidity and mortality among individuals receiving maintenance hemodialysis (HD). Fluid removal rates that exceed vascular refill rates can result in hemodynamic instability, end-organ damage to the heart, kidneys, gut and brain, among other organs, and patient symptoms. There are no known evidence-based HD treatment strategies to reduce harm from higher UF rates. Ultrafiltration profiling, the practice of varying UF rates to maximize fluid removal during periods of greatest hydration and plasma oncotic pressure, has been proposed as an HD treatment intervention that may reduce UF rate-related complications. This study is a randomized 4-phase cross-over trial in which participants are successively alternated between study arms with intervening washout periods, and treatment order is randomized. After 4-week screening and 6-week baseline periods, participants are randomized to HD with conventional UF or HD with UF profiling for a period of 3 weeks followed by a 1-week washout period before crossing over. Participants cross into conventional UF and UF profiling phases twice (2 phases per arm). The primary outcomes of interest are intradialytic hypotension (nadir intradialytic systolic blood pressure <90 mmHg), pre-to post-HD change in troponin T (expressed as a percentage), change in left ventricular global longitudinal strain (an echocardiographic measure of left ventricular systolic function), and development of intradialytic left ventricular stunning (worsening of contractile function in ≥2 segments). This study will determine the impact of UF profiling on UF rate-related cardiovascular complications in prevalent, maintenance HD patients.